Dynamics of dissolved and particulate phosphorus influenced by seasonal hypoxia in Green Bay, Lake Michigan - Lin, Peng; Klump, J. Val; Guo, Laodong (The Science of the total environment, 2016)
Despite major investments in point source reductions, portions of the Great Lakes, like Green Bay, remain hypereutrophic and are subject to persistent seasonal hypoxia. Phosphorus (P) is generally a limiting nutrient in the Great Lakes ecosystem, but not all P species are equally bioavailable, and the dynamics of nutrients and their correlation to algal bloom remain poorly characterized, in part, due to a lack of adequate quantification of P chemical speciation. During summer 2014, water samples were collected from seasonally hypoxic Green Bay for measurements of dissolved and particulate inorganic and organic P to examine P cycling dynamics along a steep nutrient gradient ranging from Fox River inflow dominated eutrophic waters in the southern bay to mesotrophic northern waters near the bay's connection with open Lake Michigan. River-derived dissolved and particulate P was quickly removed from the water column in southern Green Bay through biological uptake and sedimentation. Concentrations of phosphate or dissolved inorganic P (DIP) dramatically decreased from 828±216nM in the Fox River, comprising 57±1% of the total dissolved P, to 24±9nM in northern Green Bay where dissolved organic P (DOP) became predominant (>80%). Generally low phosphate concentrations and extremely high dissolved organic C/P ratios (2090±1160 in August 2014) suggested high DOP turnover rates and active transformation between DOP and DIP through organic degradation during P-limited conditions in Green Bay. Elevated DIP levels were accompanied by low dissolved oxygen in deeper waters (10–15m) of central Green Bay where hypoxia-development occurred, suggesting the release of DIP through particle regeneration under hypoxic conditions enhanced by lateral transport and sediment resuspension. High partition coefficients (Kd) of both inorganic and organic P and their significant negative correlation with suspended particulate matter concentrations indicated the particle-reactive nature of P in freshwater environments and may imply that DOP could also be bioavailable under P-limitation. [Display omitted] •Dissolved and particulate P speciation was studied in Green Bay, Lake Michigan.•Steep gradients in P species exist from eutrophic river to mesotrophic bay waters.•Low DIP, high DOP and high DOC/DOP ratios were observed throughout Green Bay.•Hypoxia and sediment resuspension appeared to enhance DIP release from sediments.•High particle-reactivity of P may be a factor for P-limitation in lake waters.